2020
DOI: 10.1200/po.19.00346
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Based Chemotherapy in Metastatic Prostate Cancer With DNA Repair Gene Alterations

Abstract: PURPOSE Alterations in DNA damage repair (DDR) genes occur in up to 25% of patients with metastatic castration-resistant prostate cancer (mCRPC) and may sensitize to platinum chemotherapy. We aimed to evaluate the efficacy of platinum-based chemotherapy in DDR-mutant (DDRmut) mCRPC. METHODS We assessed response to platinum chemotherapy based on DDR gene alteration status in men with mCRPC who underwent tumor and germline genomic profiling. Patients with deleterious alterations in a gene panel that included BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 32 publications
1
100
0
Order By: Relevance
“…40,41 In the DDR context, several retrospective studies suggest that BRCA2-mutated prostate cancer patients might benefit from this treatment approach. [42][43][44][45] The largest of these analyses included 141 men with mCRPC treated with carboplatin and docetaxel at the Dana Farber Cancer Institute between 2001 and 2015, and reported a benefit from this combination for patients with germline BRCA2 mutations. 43 Six out of the eight BRCA2 carriers (75%) showed a >50% decline in the levels of prostate-specific antigen (PSA) at 12 weeks, compared with 23 of 133 of non-carriers (17%) (P = 0.001).…”
Section: Targeting Ddr Genes In Prostate Cancermentioning
confidence: 99%
“…40,41 In the DDR context, several retrospective studies suggest that BRCA2-mutated prostate cancer patients might benefit from this treatment approach. [42][43][44][45] The largest of these analyses included 141 men with mCRPC treated with carboplatin and docetaxel at the Dana Farber Cancer Institute between 2001 and 2015, and reported a benefit from this combination for patients with germline BRCA2 mutations. 43 Six out of the eight BRCA2 carriers (75%) showed a >50% decline in the levels of prostate-specific antigen (PSA) at 12 weeks, compared with 23 of 133 of non-carriers (17%) (P = 0.001).…”
Section: Targeting Ddr Genes In Prostate Cancermentioning
confidence: 99%
“…DDRd, and particularly genes associated with homologous recombination, are suggested as plausible biomarkers for platinum responses in mCRPC 10 . A recent study by Mota et al described a higher proportion of PSA 50 responses to platinum‐based chemotherapy in the DDRd group when compared to DDRp patients 11 . In our study, a similar outcome was found, although the biochemical response of DDRd patients to carboplatin was largely driven by the BRCA2mut subgroup, with all seven BRCA2mut patients showing a PSA 50 response.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] A recent study demonstrated biochemical responses in half of the patients with DDRd, particularly those with BRCA2 aberrations, as well as those with alterations in PALB2, FANCA or CDK12. 11 Patients with small cell (neuroendocrine) prostate cancer (SC-NEPC) appear to show superior disease control with platinum-based regimens over standard of care taxane chemotherapy for mCRPC. 12,13 A recent study identified patients with aggressive variant prostate cancer (AVPC), as a subtype defined as either SC-NEPC or prostate adenocarcinoma with clinicopathological features associated with poor outcome, to benefit most from platinum-based regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radium-223 is not included due to the recent EMA recommendations restricting its use only to mCRPC patients who already received two treatments. Carboplatin is included despite the lack of an indication for prostate cancer since there is accumulating evidence that platinum-based chemotherapy is effective in tumors with defects in the DNA repair genes [26]. Several therapies will be available for treatment of patients in a biomarker signature, and-conversely-a given as well as one treatment can be administrated for patients with different biomarker signatures.…”
Section: Trial Designmentioning
confidence: 99%